Asymptotic behavior of solutions of a third order nonlinear differential equation - Graef, J.R.; Remili, M. (Нелінійні коливання, 2017)
The asymptotic properties of solutions of some third order differential equation are examined. Sufficient conditions for the square integrability and oscillation of solutions are established. Вивчаються асимптотичнi властивостi розв’язкiв деякого рiвняння третього порядку. Встановлено достатнi умови квадратичної iнтегровностi та осциляцiйностi розв’язкiв.